HUBUNGAN KUALITAS PELAYANAN DAN KEPUASAN TERHADAP LOYALITAS PASIEN - Sequeira, Deonizia Fatima Vong (STIKES Widyagama Husada, 2025)
Patient satisfaction and loyalty are critical for the sustainability and reputation of healthcare services. Service quality, which includes reliability, empathy, and responsiveness, plays a significant role in shaping patient experiences. Despite advancements, hospitals continue to face challenges in maintaining patient loyalty, often influenced by satisfaction derived from service quality. The aim of this study was to analyze the correlation between service quality, patient satisfaction, and loyalty among inpatients at Diamond IHC, Lavalette Hospital Malang. This study employed a cross-sectional design with a quantitative approach. Data were collected through structured questionnaires distributed to 150 inpatients, focusing on dimensions of service quality, patient satisfaction, and loyalty. Statistical analysis was conducted to identify relationships among these variables. The findings indicate a significant positive correlation between service quality and patient satisfaction, which subsequently impacts loyalty. Among the dimensions of service quality, reliability and empathy were identified as key determinants of patient loyalty. This study conclude that enhancing service quality is essential for improving patient satisfaction and fostering loyalty. Hospitals should prioritize continuous improvements in service delivery, focusing on both technical and interpersonal aspects, to build sustainable patient relationships.